2012
DOI: 10.1002/fld.3725
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of implicit and subgrid‐scale model large‐eddy simulation techniques for low‐Reynolds number airfoil applications

Abstract: SUMMARYA computational study of a high‐fidelity, implicit large‐eddy simulation (ILES) technique with and without the use of the dynamic Smagorinsky subgrid‐scale (SGS) model is conducted to examine the contributions of the SGS model on solutions of transitional flow over the SD7003 airfoil section. ILES without an SGS model has been shown in the past to produce comparable and sometimes favorable results to traditional SGS‐based large‐eddy simulation (LES) when applied to canonical turbulent flows. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(75 citation statements)
references
References 51 publications
(94 reference statements)
12
61
0
Order By: Relevance
“…The filter is applied directly to the solution (conservative variables) at every time step and acts as an implicit sub-grid scale (SGS) model that enforces dissipation of scales smaller than the filter cut-off wavelength. Garmann et al (2013) performed an extensive analysis of the ILES technique in comparison to more conventional ones with an explicit SGS model and concluded that, subject to an appropriate grid resolution, ILES simulations are capable of correctly capturing the flow physics of a flow such as the one being studied in the current study.…”
Section: Problem Description and Methodsologymentioning
confidence: 94%
“…The filter is applied directly to the solution (conservative variables) at every time step and acts as an implicit sub-grid scale (SGS) model that enforces dissipation of scales smaller than the filter cut-off wavelength. Garmann et al (2013) performed an extensive analysis of the ILES technique in comparison to more conventional ones with an explicit SGS model and concluded that, subject to an appropriate grid resolution, ILES simulations are capable of correctly capturing the flow physics of a flow such as the one being studied in the current study.…”
Section: Problem Description and Methodsologymentioning
confidence: 94%
“…SVV and low-pass filtering can also be used to address the closure problem, i.e. by introducing artificial dissipation to represent the effect of the subgrid scales [20,[24][25][26][27][28]. A technique intended solely for stabilization of high-order schemes is over-integration, also known as polynomial de-aliasing, but this incurs a high computational cost [9,29].…”
mentioning
confidence: 99%
“…23 The filtering regularization procedure provides an attractive alternative to the use of standard SGS models, and has been found to yield suitable results for several turbulent and transitional flows on LES level grids. 24 A reinterpretation of this ILES approach in the context of an Approximate Deconvolution Model 25 has been provided by Matthew et al 26 III. Numerical procedure All simulations were performed with the extensively validated high-order, Navier-Stokes flow solver, FDL3DI .…”
Section: Governing Equationsmentioning
confidence: 98%